ANALISA DAN PERANCANGAN JARINGAN PRIVATE CLOUD COMPUTING BERBASIS WEB EYEOS - Dicky Lumena; Anton Anton; Esron Rikardo Nainggolan (Jurnal Techno Nusa Mandiri, 2016)
Private Cloud Computing is the model of Cloud Computing that provides a smaller scope to be able to provide certain services to specific users on Enterprise scale companies. Expansion of the company at Sutindo Raya Mulia, PT will add new employees and new computer devices and their software application that has a license. It will lead to the use of base servers load in the company. In the Cloud Computing system base servers, local no longer has to do all the heavy load when used for all resource servers cloud computing will be the one using OpenStack. OpenStack is a cloud OS that manages the resource for a function of computing, storage, network, and can be implemented for the characteristics of Infrastructure as a Service (IAAS). OpenStack can be built through the virtual server instance for eyeOS as one of cloud computing services Software As A Service (SAAS). Computer users simply install the browser on their computer can already implement in the company by using the eyeOS.